The Use of Word Walls Technique to Improve Students’ Writing Ability in Descriptive Text - Elsa Sovia Mandasari; Syamsul Rizal; Nadrah Nadrah (Yayasan Karinosseff Muda Indonesia, 2022)
This research is about the use of word walls technique to improve students’ writing ability in descriptive text. There are some problems that faced by the students at the seventh grade students of SMPN 17 Kota Bengkulu in writing descriptive text the first is they do not have idea to write descriptive text. Second, they still confused in organizing the writing. Third, they often do some mistakes with the lack of knowledge in vocabularies. The objective of this research was to improve students’ writing ability in descriptive text using word walls technique. This research used classroom action research method that consisted of four steps, there are pre-assessment, cycle I, cycle II, and cycle III. The subject of this research was students of Class VII D in SMPN 17 Kota Bengkulu. They were 24 students that consisted of 15 male and 9 female. The instruments of this research were interview, teacher and students’ observation checklist, writing test, and documentation. Based on the finding of this research, it showed that word walls technique could improve students’ writing ability in descriptive text. Students were active in the classroom and good interaction between teacher and students. The evaluation test administrated at the end of each cycle. The result of mean score on evaluation were pre-assessment (47,65), cycle I (59,36), cycle II (67,96), and cycle III (73,95). It could be concluded that there were improvement in every cycle, a significant different between the mean score of pre-assessment and cycle III namely 47,65 and 73,95. It showed that word walls technique could improve student’s writing ability in descriptive text.